PERLINDUNGAN MASYARAKAT TERHADAP PELANGGARAN SIARAN IKLAN NIAGA PADA LEMBAGA PENYIARAN RADIO SWASTA DI KOTA SAMARINDA - Bella, Tiara Cindy Artha; Susanti , Erna; Husain , Safarni (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Violations of commercial advertising broadcast programs that are feared to be misleading and cause misperceptions that deceive the public are rampant on Private Radio in Samarinda City. Lack of understanding by Private Radio Broadcasting Institutions in Samarinda City regarding Law Number 32 of 2002 concerning Broadcasting and Broadcasting Behavior Guidelines (P3) and Broadcast Program Standards (SPS) 2012 is one of the causes. The purpose of this study is to analyze the implementation of supervision, follow-up and efforts to protect the public against violations of commercial advertising broadcast programs by private radio broadcasting institutions in Samarinda City. The results of the study indicate that first, internal supervision of the Indonesian Broadcasting Commission in the process of monitoring broadcast content has begun to run optimally, from sources representing elements of the East Kalimantan Provincial KPID, external supervision or media monitors and also industry players all have more or less the same opinion, that the East Kalimantan KPID has been quite optimal in carrying out its function as an independent State institution tasked with supervising the broadcasting system in Indonesia. Second, the public protection efforts carried out by private radio broadcasting institutions in Samarinda City against Commercial Advertising Broadcast Programs are by stopping commercial advertising broadcasts that are in conflict with applicable laws after receiving a warning from the East Kalimantan KPID.